PANEN HUJAN DAN ALIRAN PERMUKAAN UNTUK PENINGKATAN PRODUKTIVITAS PERTANIAN LAHAN KERING, PENANGGULANGAN BANJIR DAN KEKERINGAN - Gatot Irianto (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Rainfall and runoff harvesting study at the Kali Garang basin, Semarang under the cooperation program between Centre for Soil and Agroclimate,Agency of Agriculture Research and Development (CIRAD) France and Government of Central Jawa for improving soil productivity,controlling flood and drought are presented in this paper.The results show that through water harvesting it is possible to increase diversity, improving added value and decreasing agriculture risks of agriculture commodity. Moreover rehabilitation of degraded land and soil conservation practices can be promoted.